PELATIHAN PEMBUATAN PERANGKAT AJAR INTERAKTIF MENGGUNAKAN MENTIMETER - Yuli Fitrisia; Mardhiah Fadhli; Dini Nurmalasari; Wenda Novayani; Sugeng Purwantoro ESGS (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
Currently, the whole world is struggling to deal with the COVID-19 pandemic. During the pandemic, many things were affected and changed the habits of all mankind in the world, including the field of Education which changed drastically. Previously, the teaching and learning process was mostly done face-to-face in the same place or location, but now it has to be done online. During the online learning process, many problems arise from both the teacher and student. One of them is that students get bored quickly, lack of student involvement and participation in the teaching and learning process. This is a challenge for teachers how to create an interesting and interactive learning atmosphere. However, the obstacle faced by teachers is that not all teachers understand and know what media can be used to make the learning process interesting and interactive. Based on these problems, in this Pengabdian kepada Masyarakat activity, training activities for making teaching devices using a Mentimeter have been carried out for teachers of SMK Taruna Persada Dumai which was held on September 25, 2021 with a total of 16 participants. The purpose of this activity is to prepare an interesting and interactive teaching and learning process to increase student involvement and participation when the teaching and learning process is carried out online and to help partners have basic understanding and skills in using interactive learning applications. The result of this activity is an evaluation of activities that have been carried out through a questionnaire, it is found that the material presented can add insight to the teacher, in accordance with the expected competencies so that later it can be applied to the teaching and learning process. In addition, participants felt comfortable following the training because of the positive interaction between participants and presenters and the way the material was presented in an interesting way. Based on the results of the questionnaire, recommendations were also obtained for the next activity in the form of training in making learning videos and using other learning media to support the teaching and learning process.